INSTITUSIONALISASI PENGANGGARAN BERBASIS KINERJA DI BADAN PERENCANAAN PEMBANGUNAN DAERAH PROVINSI JAWA TIMUR - Ari Susanti; Mohamad Suyunus (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2018)
This research is motivated by the phenomenon of paradigm shift of budget system from the traditional to performance-based that started since the enactment of regional autonomy system. This phenomenon occurs along with the demands of good governance that want higher levels of transparency, accountability, effectiveness and efficiency of budget management. Institutionalization process according to Burns and Scapens (2000) institutional theory takes place through four stages: encoding, enacting, reproduction and institutionalisation. This research aimsto understand the process of institutionalization of performance-based budgeting in Badan Perencanaan Pembangunan Daerah Provinsi Jawa Timur. The method used in this research is qualitative method with exploratory case study approach and data collection was done through interview, observation and documentation.The results showed that the institutional position of Badan Perencanaan Pembangunan Daerah Provinsi Jawa Timur was in the reproduction stage. This is because the organization still using the old routine and habit although there have been a legal regulation in the form of guidelines issued since 2006. These conditions that causing some problems in the institutionalization of performance-based budgeting process has not run optimally. Keywords: Badan Perencanaan Pembangunan Daerah Provinsi Jawa Timur,Institutional Theory, Performance-based Budgeting